A Discourse Analysis of the Conflict Coverage in the Mainstream Media: A Case Study of Iran’s Nuclear Deal - Yoosofi, Amir (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
In an attempt to examine the possibility of a constructive communication with a country like Iran, the intention of this thesis is to acquire a diverse perspective toward the current political and cultural struggles in the relationship between the country and the wider world. Studying the very recent Iranian nuclear deal, I am hoping that this study will provide creative alternative perspectives for more constructive conflict coverage in the future. Very often the conflict between Iran and the rest of the world has been reduced to simple binary oppositions such as dictatorship vs. democracy, or new vs. traditional, or secular vs. religious. By examining discourses of the news media, we may realize possible alternative ways of shaping communication with regards to a peaceful and hospitable act that will honor the voices of the other. Through a discourse theory approach, this study reviews the coverage of the Iran’s nuclear deal in the mainstream news media; the selected media outlets are New York Times, Fox News Online Website, Kayhan and IRNA; these well-received study cases are chosen from the United States and Iran. I have tried to present the more conservative and liberal voices in addition to the more leftist ones. In this thesis, I have benefited from Derrida’s notion of deconstruction, as well as Foucault’s critical view of discourse. This thesis challenges and questions the realities that are being constructed and their relationship with knowledge and power. I argue that the coverage of the mentioned newspapers had a specific way of fixing meaning that can result in creating more tension, and ultimately violence. The aim here is to problematize the dominant discourses and to challenge any attempt of normalization. By exposing the selected texts to the social and historical context of their claims, one may be able to uncover their binary oppositional perspective, and to problematize them with foregrounding what has been backgrounded. Keywords: Iran nuclear deal, discourse analysis, New York Times, Kayhan, IRNA, Fox News, constructive conflict coverage, Peace journalism.

ÖZ: Bu tezin amacı İran gibi bir ülke ile yapıcı bir iletişim kurma imkanını inceleyerek, İran'ın mevcut siyasi ve kültürel mücadelelerine ve dünyanın geriye kalanıyla ilişkisine çok yönlü bir bakış açısı kazandırmaktır. Yakın geçmişte yapılan Iran nükleer anlaşmasını inceleyerek, çatışmalar üzerine ileriye dönük yaratıcı, yapıcı ve çok yönlü bir haber yapımı sağlamayı umuyorum. Sıklıkla Iran'la dünyanın geriye kalanıyla arasındaki fikir ayrılıkları ikili karşıtlıklar şeklinde basite indirgenmektedir, mesela, diktatörlüğe karşı demokrasi, ya da yeniye karşı geleneksel veya sekülere karşı dindar gibi. Bir çok kişi tarafından tarafsız ve açık olarak görülen New York Times'ın bile bu basite indirgeme tuzağına düştüğü gözlemlenmiştir. Haber medyasının söylemlerini inceleyerek daha barışçıl, ılımlı ve diğerlerinin seslerini de onurlandıran bir iletişimin şekillenmesinde olası alternatiflerin de farkına varılabilir. Bu tez söylem teorisi yaklaşımı ile, İran'ın nükleer anlaşmasının ana akım medyada nasıl haberleştirildiğini gözden geçirmektedir. Bu bağlamda ABD'den ve Iran'dan ana akım medya kanalları olan New York Times, Fox News Online website, Kayhan ve IRNA örnek olarak seçilerek hem muhafazakâr, hem liberal, hem de solcu görüşleri sunmayı amaçlıyorum. Bu tezde Derrida'nın yapısökümü kavramından ve Foucault'un söyleme eleştirel bakış açısından faydalanılmıştır. İnşa edilmiş gerçeklikleri ve bu inşa edilmiş gerçekliklerin güç ve bilgi arasındaki ilişkisini sorgulayan bir tezdir. Yukarıda belirtilen gazetelerin, belirli bir sekilde anlamlandırdığı haberlerin, daha fazla gerginlik ve hatta şiddet yaratarak sonuçlanacağını savunuyorum. Buradaki amaç, baskın söylemi problematize ederek herhangi bir normalleştirme çabasını reddetmektir. Ancak seçilmiş yazıların sosyal ve tarihsel bağlamdaki iddialarına ışık tutulursa barındırdıkları ikili karşıtlıklar ortaya çıkacak ve geri plana itilmiş olan açığa çıkacaktır. Anahtar Kelimeler: İran'ın Nükleer Programı, Söylem Analizi, New York Times, Kayhan, IRNA, Fox News, Barış Gazeteciliği
Master of Arts in Communication and Media Studies. Thesis (M.A.)--Eastern Mediterranean University, Faculty of Communication, Dept. of Communication and Media Studies, 2016. Supervisor: Assoc. Prof. Dr. Tuğrul İlter.
Keywords: Communication and Media Studies; Mass Media-Conflict Coverage-Iran; Iran nuclear deal; discourse analysis; New York Times; Kayhan; IRNA; Fox News; constructive conflict coverage; Peace journalism